Uma crise à lá Minsky?: uma análise da crise financeira sob a ótica de Hyman Minsky - Gzvitauski, Tatiana Rimoli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Capitalism reproduces itself through contradictory processes. The system, in its latest phase of financialized accumulation tends to speculative crisis that market mechanisms are not able to regulate. This is the post-Keynesians theoretical argument that intend to investigate what behaviors determine and aggravate the crisis. After the crisis that had trigger in the US financial system, the Post Keynesian Hyman Minsky (1919 - 1996), little explored so far, returned to the discourses of the function of the financial system and its regulation. For many, the road taken by the world economy and the breakdown of the financial system fit into the analysis of the author as to be possible to consider that there was a Minsky moment: a deep and sudden collapse preceded by lull and calm. Through the characterization of Minsky's methodology, this dissertation aims to advance the understanding of the financial system in search for the causes and remedies of Minsky fragility illustrated by the recent subprime crisis

O capitalismo se reproduz através de processos contraditórios. O sistema, em sua fase mais moderna, de acumulação financeirizada, tende a crises especulativas que os mecanismos de mercado não são capazes de regular. Esse é o argumento de teóricos da corrente pós-keynesiana que se propõem a investigar quais comportamentos geram e agravam crises financeiras. Depois da crise iniciada no sistema financeiro norte-americano, Hyman Minsky (1919-1996), pouco abordado até então, voltou ao debate sobre o funcionamento do sistema financeiro e sua regulamentação. Para muitos, a trajetória percorrida pela economia mundial e a ruptura do sistema financeiro se enquadram nas análises do autor, a ponto de ser possível considerar ter havido um Momento Minsky: um profundo e repentino colapso precedido por calmaria e bonança. Através da caracterização da abordagem de Minsky, essa dissertação se propõe a avançar no entendimento do sistema financeiro à procura das causas e corretivos da fragilidade financeira ilustrada pela crise subprime recente
Keywords: Minsky, Hyman P. 1919; Capitalismo; Economia; Crise financeira; Financial crises